Properties and Phase Structure of Polycaprolactone‐Based Segmented Polyurethanes with Varying Hard and Soft Segments: Effects of Processing Conditions. Issue 2 (16th November 2017) - Imre, Balazs; Gojzewski, Hubert; Check, Casey; Chartoff, Richard; Vancso, G. Julius
Abstract: A series of segmented polycaprolactone polyurethane (PU) polymers is synthesized. One set of polymers ranges in composition from 0 to 100 wt% hard segments (HSs). The syntheses are carried out in solution and the polymers are melt‐processed by compression molding. Another subset of polymers is formed in bulk from a blocked isocyanate prepolymer. The blocked polymer's thermal and mechanical properties are compared with the melt‐processed materials. The emphasis in this paper is on the effects of varying the chemical structures of the PUs on their phase structures and physical cross‐linking due to nanocrystalline hard domains. The thermal properties indicate that nanophase separation and the formation of hard domains occur at HS contents above ≈8 wt%. Property differences resulting from varying the hard segment amounts are directly related to differences in morphology at the nanoscale. Atomic force microscopy images show that the best elastomeric mechanical properties are found when nanocrystallites are 4–5 nm in size. Abstract : A series of polycaprolactone segmented polyurethanes (PUs) polymerized both in solution and bulk from blocked isocyanate prepolymers is the focus of this study. The effects of varying the chemical structure and processing of the PUs on their phase structure are evaluated. Differences in properties due to processing are related to morphology which includes rod‐like nanocrystallites.